70. Universal Instructional Design Principles for Moodle - Elias, Tanya (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
This paper identifies a set of universal instructional design (UID) principles appropriate to distance education (DE) and specifically tailored to the needs of instructional designers and instructors teaching online. These principles are then used to assess the accessibility level of a sample online course and the availability of options in its LMS platform (MoodleTM) to increase course accessibility. Numerous accessibility-sensitive plug-in modules are found to be available to Moodle users, though relatively few features were included in the sample course analysed. This may be because they have not been made available to instructors at the institutional level. The paper offers a series of recommendations to improve the accessibility of online DE to learners with diverse abilities, disabilities, and needs.